Disability in leprosy patients in a Central-Western Brazilian Reference Center in the period of 2000-2002 - Corrêa, Célia Maria de Jesus (2006)
A descriptive and retrospective study was carried out with data collected from clinical fi les of 282 citizens with leprosy attended in the Hospital São Julião, Campo Grande, Mato Grosso do Sul, Brazil during 2000 and 2002. The study aim was to verify the occurrence of disability and associate it with age, operational classifi cation and place of residence. The data was tabulated and the frequencies calculated. Ages from the patients investigated ranged from 20 to 80 years, 52.1% were born in Mato Grosso do Sul, 70.6% lived in Campo Grande; 63% were males and 53% had some degree of disability. Multidrug therapy was given to 56% of the patients, 50% were referred to São Julião Hospital, 22.0% were contacts and only 11.7% looked for the São Julião Hospital by spontaneous de-mand. Degree of disability 2 was higher within the state of Mato Grosso do Sul (29,8%) than in the capital (10,5%). Patients who received multidrug therapy showed greater degrees of disability 1 or 2 (GIF 1 or 2) at the time of admission. The results indicate that the treatment offered at the Hospital was considered good, based on number of patients under multidrug therapy (100%), a high rate of motor and sensitive assessment (92.55%).